Organisational politics on job satisfaction: An empirical study of police officials in a selected police service station - Wiza Munyeka; Sam T. Setati (Africa’s Public Service Delivery & Performance Review, 2022)
Background: The phenomenon of organisational politics is widely recognised in organisations, and it can have a significant impact on job satisfaction. A negative organisational variable, organisational politics alters the organisational environment, culture and behaviour. The study of organisational politics is proliferating and is now a popular research topic. In terms of job satisfaction, this can be divided into two different categories: hygiene and motivation. The purpose of this study is to explore how organisational politics affect motivational and hygiene factors in relation to job satisfaction.